Steer gains on burned and nonburned bluestem pasture and reimplanting with Ralgro at mid-summer - Smith, E.F.; Behnke, R.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2011)
Steers on a late spring burned bluestem pasture gained 1.4 lbs daily during the summer compared with 1.0 lb. by steers on a nonburned pasture. All steers were implanted with Ralgro at the start of the grazing season (May 1) and half in each pasture were reimplanted July 15. Reimplanting did not affect weight gain.
Keywords: Beef; Gain; Steer; Implants; Burned vs nonburned bluestem